Prevalence of Asymptomatic Peripheral Arterial Disease and Related Risk Factors in Younger and Elderly Patients in Taiwan. (May 2014) - Chen, Yi-Jen; Lin, Ming-Shian; Hsu, Kun-Yen; Chen, Cheng-Ren; Chen, Chuan-Mu; Chen, Wei
We determined the prevalence of asymptomatic peripheral arterial disease (PAD) and cardiovascular risk factors in Taiwan. Ambulatory participants (n = 1915) without symptoms of PAD were enrolled (mean age of 61.2 years). The ankle-brachial index (ABI) was used to detect the PAD (ABI < 0.90). The overall prevalence of asymptomatic PAD was 5.4% (2.8% in the younger participants [<65 years of age, n = 1021] and 8.4% in the elderly participants [≥65 years of age, n = 894]). Younger participants with asymptomatic PAD had a significantly higher rate of hypertension (55.2% vs 30%) and obesity (31% vs 13.3%) than those without asymptomatic PAD ( P < .05). Elderly participants with asymptomatic PAD had a significantly higher rate of diabetes mellitus (36% vs 21.2%) and hypertension (69.3% vs 55.4%) than those without asymptomatic PAD ( P < .05). Asymptomatic PAD is prevalent among elderly Taiwanese individuals. Overall, age was the strongest risk factor for the development of asymptomatic PAD.